2009
DOI: 10.1002/esp.1785
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal soil aggregate stability variation in relation to rainfall and temperature under Mediterranean conditions

Abstract: Aggregate stability, one of the main factors controlling soil erodibility, varies over time. Knowledge of its variation would help to identify better soil management practices. In 10 soils from central Greece devoted to cereal cropping, seasonal wet aggregate stability (WAS) fluctuations were investigated over a period of two successive years. The wet-sieving technique of airdried aggregates was used for WAS determinations, according to a test resulting in an instability index calculation. Over the first year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
5
25
0
Order By: Relevance
“…Seasonal dynamics in soil aggregation are affected both by weather differences between the sampling years and by bioenergy system management. Dry periods increase aggregate stability (Dimoyiannis, ) and precipitation events can disrupt macroaggregates, which is consistent with our observations. In both years, corn systems experienced aggregate disruption between May and July sampling dates, with slight aggregate rebuilding in August.…”
Section: Discussionsupporting
confidence: 92%
“…Seasonal dynamics in soil aggregation are affected both by weather differences between the sampling years and by bioenergy system management. Dry periods increase aggregate stability (Dimoyiannis, ) and precipitation events can disrupt macroaggregates, which is consistent with our observations. In both years, corn systems experienced aggregate disruption between May and July sampling dates, with slight aggregate rebuilding in August.…”
Section: Discussionsupporting
confidence: 92%
“…The observed seasonal 311 dynamics in total aggregate loss seemed to be related to rainfall distribution with lower losses under 312 dry, summer conditions, and higher losses in spring and autumn with higher soil water content 313 (Figure 2, 4). This seasonal pattern was in line with numerous field studies where greater aggregate 314 stability was recorded in summer with respect to autumn and early spring (Bullock et al 1988;315 Blackman 1992;Chan et al 1994;Dimoyiannis 2009;Algayer et al 2014). 316…”
Section: Discussion 257supporting
confidence: 85%
“…In alpine grasslands, proportions of soil aggregates were generally influenced by both GST and GSP. Similar findings were also reported by Rillig et al (2002), who found that increasing temperature could decrease soil aggregate water stability by stimulating the role of arbuscular mycorrhizal fungi in soil aggregation in an annual grassland in northern California, USA, and by Dimoyiannis (2009), who reported that total monthly precipitation and mean monthly air temperature strongly correlated with seasonal soil aggregate stability in the Thessaly Plain, central Greece.…”
Section: The Effect Of Climate Factorssupporting
confidence: 87%
“…Soil pH affected by the climate factors has been found in many natural ecosystems (Barton et al, 1994), which is also confirmed in alpine grasslands in Tibet in the present study. Soil aggregate is a dynamic soil property, which varies over time, partially depending on climatic processes (Dimoyiannis, 2009). In alpine grasslands, proportions of soil aggregates were generally influenced by both GST and GSP.…”
Section: The Effect Of Climate Factorsmentioning
confidence: 99%